Insightfully Explore the Ethical Decision Making of Tax Consultants During COVID-19 Pandemic - Pramana, I Kadek Adhi; Budiasih, I Gusti Ayu Nyoman; Dwirandra, Anak Agung Ngurah Bagus; Putri, I Gusti Ayu Made Asri Dwija (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022), 2022)
Weakening economic performance during COVID-19 pandemic has an impact on state revenues in the tax sector caused dilemma for a tax consultant. This study aims to explore various ethical decisions making by tax consultants. Transcendental phenomenology Husserl's is used to obtain pure consciousness from informants. Data was collected by interview and based on the interpretation, the dilemma caused by non-optimal income and client's internal policies. In addition, several clients experience tax audits during the pandemic. Ethical assessment of decision making is considered into several aspects, such as: moral considerations, commitment to providing optimal services, and awareness that the role of tax consultants is helping the government to gain state revenue in tax sector. This study provides the relevance use of ethical theory and the theory of planned behaviour. For practitioners, this research can be used as advice in making decisions both in pandemic situations and other unexpected events. Keywords: phenomenology, dilemma, tax consultant, explore, ethical decision